2014
DOI: 10.2478/intag-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic properties of water sorption isotherms of grape seed

Abstract: A b s t r a c t. In this study the moisture sorption isotherm of grape seed was determined by using a static gravimetric method at 35-65°C and 0.108-0.821 water activity range. The sorption isotherms were found to be typical sigmoid shape of most food materials. Five models including the Brunauer-Emmett-Teller (2-parameter), Guggenheim, Anderson and De Boer (3-parameter), Oswin (2-parameter), and Peleg (4-parameter) models were considered to fit the experimental data. The FerroFontan and Peleg equations (at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The Peleg equation gives the best fit for both insects and can be used for predicting the water activity of the insects studied in this work. The same observation was done for others products such as melon seeds (Cucumis melo) (Mallek-Ayadi al., 2020), argan leaves (Argania spinosa (L)) (Ennoukh et al, 2022), grapes seeds (Vitis vinifera) (Majd et al, 2014), rice (Bingol et al, 2012) and red tilapia viscera (Oreochromis spp.) (Camaño et al, 2021).…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…The Peleg equation gives the best fit for both insects and can be used for predicting the water activity of the insects studied in this work. The same observation was done for others products such as melon seeds (Cucumis melo) (Mallek-Ayadi al., 2020), argan leaves (Argania spinosa (L)) (Ennoukh et al, 2022), grapes seeds (Vitis vinifera) (Majd et al, 2014), rice (Bingol et al, 2012) and red tilapia viscera (Oreochromis spp.) (Camaño et al, 2021).…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…They reported that the GAB model predicted experimental data more accurately. Majd et al (2014) studied the thermodynamic properties of water sorption isotherms of grape seed. Those researchers claim that the Ferro-Fontan and Peleg models, due to greater R 2 values (or lowest standard error), were chosen as a best fitted models to predict experimental data.…”
Section: Introductionmentioning
confidence: 99%